Empoderamiento personal y colectivo de la mujer campesina a través de la participación equitativa en el corregimiento de Barragán, municipio de Tuluá, Valle. Empoderamiento mujer campesina de Barragán, Valle (2021)
The objective of the research project is to make visible the skills and capacities of peasant women in the Barragán Valle district, given the need that women present with respect to their unvalued role, in addition to the fact that unmet individual and collective needs are evident; As Abraham Maslow addresses it in the hierarchy of needs, in the same way, through Manfred Max Neef's theory of the classification of needs, it was possible to find certain satisfiers that supplied said needs through the empowerment of women. With the participatory action research method and a critical / social approach, it is possible to experience the reality presented, and in this way not only addresses the needs but also makes visible the skills and functions that rural women have, through the conformation of a collective "Frutos de la Mujer Campesina Barragueña" satisfying needs such as: the sense of belonging, where each and every one of the participants shared their knowledge, ideas and contributed from their capacities, highlighting their skills not only domestic but agricultural, business and caring for the environment, in addition to well-being, by feeling valued within their community for the same participation that is exercised in it, these needs being satisfied permeated by the empowerment exercised in each of the activities carried out.